Correlation between the Use of Shared Goods with Pediculosis Capitis among Students in Pondok Pesantren Subulussalam Palembang - Rifka Purnama Sari; Dwi Handayani; Gita Dwi Prasasty; Chairil Anwar; Fatmawati Karim (Faculty of Medicine, University of Jember, 2022)
Pediculosis capitis is a parasitic infection caused by the parasite Pediculus humanus var. capitis, which commonly found in densely crowded areas such as boarding schools. It is possible to contract pediculosis capitis by coming into direct or indirect contact with sufferers' hair. The goal of this study was to assess the prevalence of pediculosis capitis in students at Pondok Pesantren Subulussalam Palembang, as well as the association between the use of shared goods and the occurrence of pediculosis capitis. This study is a cross-sectional observational analytic study including 116 students who live permanently in Pondok Pesantren Subulussalam Palembang. A questionnaire was used to collect data, as well as direct observation of hair samples. The Chi-Square test, Fisher's exact test, and logistic regression were used to examine the results. The findings revealed that 35.3% of people had pediculosis capitis, and that there was a significant association between the use of mattresses (p=0.007), combs (p=0.024), and shared veils (p=0.006) and the occurrence of pediculosis capitis. The use of combs (p=0.018) and shared veils (p=0.001) were the most influential variables on the occurrence of pediculosis capitis, according to the results of the logistic regression test. The spread of pediculosis capitis disease is predicted to be reduced and prevented with improved personal hygiene, environment sanitation, and treatment. Keywords: Pediculosis capitis, boarding schools, Subulussalam, shared goods